2020
DOI: 10.1186/s12879-020-05661-9
|View full text |Cite
|
Sign up to set email alerts
|

The clinical characteristics and outcome of cryptococcal meningitis with AIDS in a tertiary hospital in China: an observational cohort study

Abstract: Background Despite the profound impact of antiretroviral therapy in the control of AIDS mortality, central nervous system opportunistic infections remains a significant burden in AIDS patients. This retrospective study aims to elucidate the clinical characteristics, outcome and risk factors of cryptococcal meningitis (CM) poor prognosis in AIDS patients from a tertiary hospital in China. Methods Clinical data from 128 patients admitted in Beijing Ditan Hospital, Capital Medical University from November 2008 t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
2
14
2
2
Order By: Relevance
“…Impaired consciousness and stiff neck are common clinical manifestations and symptoms in patients with CM, and their incidence was significantly higher in patients with unfavorable outcomes [ 25 ]. Wu et al reported that the presence of impaired consciousness increased the risk of poor prognosis by a factor of 4.4 [ 24 ]. High urea nitrogen level is often a manifestation of abnormal renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired consciousness and stiff neck are common clinical manifestations and symptoms in patients with CM, and their incidence was significantly higher in patients with unfavorable outcomes [ 25 ]. Wu et al reported that the presence of impaired consciousness increased the risk of poor prognosis by a factor of 4.4 [ 24 ]. High urea nitrogen level is often a manifestation of abnormal renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to several previous studies which have also identi ed some similar risk factors associated with poor prognosis in CM patients [9,[21][22][23][24][25], the present study differs in the following aspects: 1) All of our study participants were HIV-infected persons while the study participants in the majority of previous studies were HIV-negative persons, and the total number of participants in this study was 555, which is a relatively large sample size with regards to these types of studies. 2) Some studies chose neurocognitive impairment, seizures, neurological sequelae, relapse, or treatment effectiveness as outcome indicators in their analysis of risk factors for HIV/CM, rather than death as an outcome.…”
Section: Discussionmentioning
confidence: 77%
“…Impaired consciousness and stiff neck are common clinical manifestations and symptoms in patients with CM, and their incidence was signi cantly higher in patients with unfavorable outcomes [25]. Wu et al reported that the presence of impaired consciousness increased the risk of poor prognosis by a factor of 4.4 [24]. High urea nitrogen level is often a manifestation of abnormal renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Біохімічне дослідження ліквору виявило підвищення вмісту білку -0,6 (0,3-1,0) г/л, а також зниження концентрації глюкози -2,3 (1,4-2,9) ммоль/л. Зазначені зміни є харак-терними для даного захворювання і не відрізняються від даних інших досліджень [9,14,15,16 На наступному етапі аналізу ми порівняли вихідні дані хворих, які померли (група 1), а також тих, стан яких покращився і вони були виписані з відділення (група 2).…”
Section: рис 2 розподіл вихідного характеру ліквору за плеоцитозомunclassified